Hydrogen bonding and topological network effects on optimizing thermoplastic polyurethane/organic montmorillonite nanocomposite foam. (6th January 2021) - Lan, Bin; Li, Pengzhi; Luo, Xiehuai; Luo, Heng; Yang, Qi; Gong, Pengjian
Abstract: Foaming behavior of thermoplastic polyurethane (TPU) is extremely difficult to be regulated due to the special microphase-separation structure. Therefore, organic montmorillonite (O-MMT) was applied in TPU foaming to regulate cell nucleation, growth and stabilization simultaneously: (1) strong interfacial interaction between O-MMT with TPU could not only facilitate O-MMTs' nanoscale dispersion but also ensure a similar cell nucleation at various O-MMT loading, which effectively decoupled the complicated influences of cell nucleation and growth on TPU foam's shrinkage; (2) TPU/O-MMT topological network was constructed by O-MMT loading, regulating cell growth and corresponding decreasing cell size; (3) -OH group on O-MMT surface could hydrogen bond with TPU molecular chains in soft/hard segments, stabilizing TPU molecular chains and finally reducing foams' shrinkage. Combining hydrogen bonding and topological network resulted from O-MMT, it enables us to optimize TPU foam structure by controlling cell nucleation, growth and stabilization simultaneously, the optimal O-MMT loading was 1 wt%. Graphical abstract: Image 1 Highlights: Strong interfacial interaction facilitated O-MMTs' nanoscale dispersion in TPU. TPU/O-MMT topological network has been constructed to well regulate cell growth. Hydrogen bonding between TPU and O-MMT is beneficial to foams' cell stabilization. O-MMT regulated foams' cell growth/stabilization without affecting cell nucleation.